Leadership Agility and Organizational Resilience: An Empirical Study on SMEs in the Manufacturing Sector - Budi Raharja , Arif (Yayasan Kreatif Indonesia Emas, 2024)
This study investigates the critical role of leadership agility as a catalyst for organizational resilience in small and medium-sized enterprises (SMEs) within Indonesia’s manufacturing sector. In an increasingly volatile, uncertain, complex, and ambiguous (VUCA) global environment, SMEs are particularly vulnerable to external shocks, such as supply chain disruptions, technological obsolescence, and economic downturns. Through a rigorous mixed-methods research design, which combines a quantitative survey of 200 SME leaders with qualitative, in-depth interviews with 12 business owners and operational managers, this research identifies the core behavioral competencies and strategic decision-making patterns that enable businesses to not only survive but also thrive amidst disruptions. The study provides strong empirical evidence that agile leadership practices—specifically adaptive planning, emotional intelligence, and decentralized decision-making—are positively and significantly correlated with key indicators of organizational resilience, including business continuity, innovation capacity, and employee retention. The findings underscore that leadership agility is not merely an optional skill set but a fundamental strategic imperative for building long-term, sustainable resilience. This paper concludes with actionable recommendations for policymakers and industry associations to integrate agility frameworks into entrepreneurship training and leadership development programs, thereby strengthening the foundation of Indonesia's manufacturing backbone.